2014
DOI: 10.3892/br.2014.408
|View full text |Cite
|
Sign up to set email alerts
|

Method of isolation and characterization of Girardia tigrina stem cells

Abstract: Abstract. Tissue regeneration is widely studied due to its importance for understanding the biology of stem cells, aiming at their application in medicine for therapeutic and various other purposes. The establishment of experimental models is necessary, as certain invertebrates and vertebrates have different regeneration abilities depending on their taxon position on the evolutionary scale. Planarians are an efficacious in vivo model for stem cell biology, but the correlation between planarian cellular and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Girardia tigrina is a freshwater planarian species native to America, and has been introduced to other continents such as East Asia and Europe. Due to its large body size (approximately 10 mm in length), fast asexual reproductive rate and easy large-scale cultivation in the laboratory, G. tigrina has become an important model organism in many research fields such as development, stem cell, regeneration, neurogenesis and toxicology (Lopes et al 2015 ; Bach et al 2016 ). In this study, we reported the complete mitochondrial genome of G. tigrina and relevant phylogenetic analysis for the first time (GenBank accession No: MW972220).…”
mentioning
confidence: 99%
“…Girardia tigrina is a freshwater planarian species native to America, and has been introduced to other continents such as East Asia and Europe. Due to its large body size (approximately 10 mm in length), fast asexual reproductive rate and easy large-scale cultivation in the laboratory, G. tigrina has become an important model organism in many research fields such as development, stem cell, regeneration, neurogenesis and toxicology (Lopes et al 2015 ; Bach et al 2016 ). In this study, we reported the complete mitochondrial genome of G. tigrina and relevant phylogenetic analysis for the first time (GenBank accession No: MW972220).…”
mentioning
confidence: 99%